The circadian variation in Anti-Müllerian hormone in patients with polycystic ovary syndrome differs significantly from normally ovulating women. - Leif Bungum (Public Library of Science (PLoS), 2013)
Objective [corrected] To improve the biologic understanding of the Polycystic Ovarian Syndrome (PCOS) condition by examining the circadian variation and relationship between Anti Müllerian Hormone (AMH), gonadotropins and ovarian steroids in PCOS patients compared to normally ovulating and menstruating women. By comparing the pattern of co-variation between AMH and Luteinizing Hormone, two compounds closely linked to hyperandrogenism and anovulation in PCOS, the involvement of the Hypothalamic-Pituitary-Ovarian axis in PCOS pathology could be elucidated. Patients Eight normal-weighted young, anovulatory PCOS-women as study group and ten normal menstruating and ovulating women as controls. Interventions Observational prospective study of the circadian variation in AMH, gonadotropins, sex steroids and androgens in a study and a control group. A circadian profile was performed in each study and control subject during a 24-h period by blood sampling every second hour, starting at 8:00 a.m. and continuing until 8:00 a.m. the following day. Results Significant differences in hormonal levels were found between the groups, with higher concentrations of AMH, LH and androgens in the PCOS group and lower amounts of FSH and progesterone. A distinct difference in the circadian variation pattern of AMH and LH between PCOS patients and normal controls was seen, with PCOS patients presenting a uniform pattern in serum levels of AMH and LH throughout the study period, without significant nadir late-night values as was seen in the control group. In PCOS women, a significant positive association between LH/ FSH and testosterone was found opposite to controls. Main outcome measures Circadian variation in Anti-Müllerian Hormone, gonadotropins and ovarian steroids and the covariation between them. Conclusion A significant difference in the circadian secretion of LH and AMH in PCOS women compared to normally ovulating women indicate an increased GnRH pulse, creating high and constant LH serum concentrations. A significant co-variation between LH and AMH may suggest LH as a factor involved in the control of AMH secretion.